Nanoantibiotics Based in Mesoporous Silica Nanoparticles: New Formulations for Bacterial Infection Treatment - Elena Álvarez; Blanca González; Daniel Lozano; Antonio L. Doadrio; Montserrat Colilla; Isabel Izquierdo-Barba (MDPI AG, 2021)
This review focuses on the design of mesoporous silica nanoparticles for infection treatment. Written within a general context of contributions in the field, this manuscript highlights the major scientific achievements accomplished by professor Vallet-Regí's research group in the field of silica-based mesoporous materials for drug delivery. The aim is to bring out her pivotal role on the envisage of a new era of nanoantibiotics by using a deep knowledge on mesoporous materials as drug delivery systems and by applying cutting-edge technologies to design and engineer advanced nanoweapons to fight infection. This review has been divided in two main sections: the first part overviews the influence of the textural and chemical properties of silica-based mesoporous materials on the loading and release of antibiotic molecules, depending on the host-guest interactions. Furthermore, this section also remarks on the potential of molecular modelling in the design and comprehension of the performance of these release systems. The second part describes the more recent advances in the use of mesoporous silica nanoparticles as versatile nanoplatforms for the development of novel targeted and stimuli-responsive antimicrobial nanoformulations for future application in personalized infection therapies.